Aplicativo móvel sara no tratamento da tuberculose - Araújo, Mariana Pereira da Silva (2023)
Introduction: Tuberculosis (TB) is a chronic transmissible disease that mainly affects emerging countries due to the lack of minimal infrastructure and difficulties in accessing quality health services. It is a transmissible infectious disease caused by the microorganism Mycobacterium tuberculosis or Koch's Bacillus (BK). Objective: to evaluate a mobile application in the treatment of people with tuberculosis. Methodology: this research is the result of a partnership between the Federal University of Espírito Santo and the Federal Institute of Espírito Santo with the project entitled Innovative Technologies applied to Tuberculosis and HIV surveillance, which proposes the development and validation of innovative technologies for the disease surveillance and evaluation of the incorporation of new technologies in the Unified Health System (SUS). This is a quantitative research carried out in 03 stages. Step 1 consists of building and validating the SARA application, Step 2 a usability study of the application. The randomized clinical trial resulted in article 3. Results: in article 1, the application was built in its final version after three steps of the Delphi Technique. In the Delphi 3 stage, the global Content Validity Index was 0.92, being evaluated by seven expert judges in the North, Northeast, Midwest, South and Southeast regions and validated by six people with tuberculosis attended, reaching an Index of Global Content Validity of 0.98. In article 2, based on the scores obtained in the SURE Questionnaire, the participants agreed that the help given by the application was useful. And, finally, in article 3, it was possible to establish a clinical protocol for a randomized pragmatic trial. Conclusion: The application was validated for its content and semantics by expert judges, from a multidisciplinary perspective, and active in the field of tuberculosis in more than one region of Brazil and by the target audience for which it is intended, being considered an important tool to add to the control strategies for the end of tuberculosis. This study characterizes an important indication that the SARA application can be widely tested.